Synthesis and transition metal complexes of 3,3-bis(1-vinylimidazol-2-yl) propionic acid, a new N,N,O ligand suitable for copolymerisation - Peters, Liv; Tepedino, Fatima; Haas, Thomas; Heinemann, Frank Wilhelm; Wolf, Marion; Burzlaff, Nicolai (Inorganica Chimica Acta, 2011)
The new N,N,O heteroscorpionate ligand 3,3-bis(1-vinylimidazol-2-yl) propionic acid (Hbvip) (5) was synthesised in five steps starting from 1-vinylimidazole. This ligand is closely related to 3,3-bis(1-methylimidazol-2- yl)propionic acid (Hbmip), but contains two vinyl linker groups which can be used for radical-induced polymerisation reactions. The κ -N,N,O coordination behaviour of 5 was proven by the synthesis of the tricarbonyl complexes [Re(bvip)(CO) ] (6), [Mn(bvip)(CO) ] (7) and [Cu(bvip) ] (8). To obtain good yields of 6, it was synthesised in water instead of THF. The ligand as well as all three complexes were characterised by X-ray crystallography. Copolymerisation of 5 with pure methyl methacrylate (MMA) or a combination of MMA and ethylene glycol dimethacrylate (EGDMA) led to the solid phases P1 and P2. Polymer-bound rhenium and manganese tricarbonyl complexes could be obtained by the reaction of deprotonated P1 with [MBr(CO) ] (M = Re, Mn) and also by copolymerisation of 6 and 7 with MMA. In both cases, the facial tripodal binding behaviour was evidenced by IR spectra of the polymers. Furthermore, the content of metal incorporated in the polymers was determined by elemental analysis, AAS or ICP-OES measurements. Reaction of the deprotonated solid phase P1 with copper(II) chloride led to a blue solid-phase (P1-Cu). The UV-Vis absorption maximum of P1-Cu is found at 615 nm, which is almost identical to that found for 8. Thereby, it seems likely that P1 is flexible enough to form bisligand complexes with copper(II). This means that the copper centres act as a kind of crosslinking agents. In contrast, the heterogeneous reaction of P2 with copper(II) chloride yielded a lime green solid phase (P2-Cu). The bathochromic shift of the absorption maximum by 102 nm suggests one-sided bound copper centres. © 2011 Elsevier B.V. All rights reserved.